Protic plastic crystal/PVDF composite membranes for Proton Exchange Membrane Fuel Cells under non-humidified conditions. (1st September 2017) - Díaz, M.; Ortiz, A.; Pringle, J.M.; Wang, X.; Vijayaraghavan, R.; MacFarlane, D.R.; Forsyth, M.; Ortiz, I.
Abstract: Composite membranes based on the protic plastic crystal N, N -dimethylethylenediammonium triflate [DMEDAH][TFO] and poly(vinylidene fluoride) (PVDF) nanofibers have been developed for proton exchange membrane fuel cells (PEMFCs) under non-humidified conditions. The effect of addition of 5 mol% triflic acid or 5 mol% of the base N, N -dimethylethylenediamine on the thermal and transport properties of the material is discussed. The acid-doped plastic crystal reports more than double the ionic conductivity of the pure plastic crystal. The effects of doping the plastic crystal and the composites, with acid or base, on the ionic conductivity and fuel cell performance are reported. Composite membranes based on PVDF nanofibers and [DMEDAH][TFO] were tested in a single PEMFC. The results show the potential of these composite membranes to be used as electrolytes in this electrochemical application without external humidification.